Caracterização fenotípica e molecular de Acinetobacter baumannii isolados de pacientes de UTIs de Goiânia, com relação à capacidade de formar biofilmes e resistência aos carbapenêmicos. - Castilho, Suellen Rocha Araújo (2013)
The species Acinetobacter baumannii is the most important representative of the genus, being globally considered the pathogen of larger relevance, within the complex A. baumannii – A. calcoaceticus, to healthcare institutions worldwide. Its clinical significance has increased in recent years partly due to its notable capacity of adherence to surfaces due to presence of structures such as pili, production of EPS (exopolysaccharides) and presence of genes that favor biofilm formation, providing larger adhesion between the cells and consequent resistance to the antimicrobials. Another important characteristic is its capacity to regulate or to acquire antibiotic resistance, specifically through oxacilinases, encoded by the gene OXA, that presents potent hydrolytic activity against penicilinase-resistant penicillins. Until the moment, 250 types of OXA were already described. The expression of OXA genes can be increased in the presence of the insertion element ISAba1, which when located upstream of the gene, confer a selective advantage for the isolate when this depends on the efficient expression of a variety of resistance genes. In its absence, the resistance is usually expressed in the presence of two or more OXA genes. The capacity of biofilm formation and the presence of the genes blaPER-1, OXA-23, OXA-40, OXA- 51, OXA-58 and ISAba1 were investigated among 84 isolates from 64 patients of the Intensive Care Units of Goiânia. It was observed that 78.5% of the isolates formed biofilm, of which 23% presented the gene blaPER-1. The presence of OXA-51 gene was detected in all isolates, whereas 64.3% of the isolates had the OXA-23 gene and 24.0% of the isolates had the OXA-58 gene. The ISAba1 gene was detected upstream of the OXA-51, OXA-23 and OXA-58 genes in 33.3% (28/84), 92.6% (50/54) and 10.0% (2/20) of the isolates, respectively. None of the isolates studied presented the gene OXA-40. Of the 62 isolates resistant to imipenem and meropenem, 76.0% possessed the OXA-23 gene while 24.2% of the isolates possessed the OXA-58 gene. Of these isolates, 79.0% (49/62) presented the gene ISAba1. In the present study, the blaPER-1 gene presence was not associated with the biofilm formation, while the presence of OXA genes was related to resistance in Acinetobacter baumannii.